Rational and Social Theories as Complementary Explanations of Communication Media Choices: Two Policy-Capturing Studies - Webster, Jane; Treviño, Linda Klebe (Academy of Management Journal, 1995)
Recent media choice research has focused on attempts to determine what theory best explains people's choices of communication media. Two within-subject policy-capturing studies support the notion that media richness and social influence theories are complementary rather than competing and that the relative importance of choice factors depends on the medium. A comparison of policy-capturing and survey findings points to policy capturing as a useful research methodology. Results also suggest that rational and social factors should be included in comprehensive models of media choice that address both traditional and new media.